1997
DOI: 10.1246/bcsj.70.821
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Bis(5,5-diphenylhydantoinato)copper(II) Complexes with Primary Amines Involving Square Pyramidal CuN4O Chromophores

Abstract: Copper(II) complexes [CuL2(i-PrNH2)2·H2O] (1a), [CuL2(i-PrNH2)2] (1b), [CuL2(EtNH2)2·H2O] (2a), [CuL2(EtNH2)2]·CHCl3 (2b), [CuL2(EtNH2)2·H2O]·2CHCl3 (2c), and [CuL2(EtNH2)2·MeOH] (2d) (L = 5,5-diphenylhydantoinate) have been prepared. The crystal structures of 1a, 2c, and 2d were determined by X-ray analysis. Each CuN4O chromophore is a five-coordinated square-based pyramidal geometry. The axial Cu–O distances are Cu(1)–O(1)(water) = 2.362(10) Å, Cu(1)–O(1)(water) = 2.436(9) Å and Cu(1)–O(1)(MeOH) = 2.33(1) Å,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Xilan Hu, Qing Jiang, Daqi Wang and Haifeng Liu S1. Comment 5,5-Diphenylimidazoline-2,4-dione (phenytoin) is a widely used drug in the treatment of epilepsy and an excellent ligand for transition metal complexes (Milne et al, 1999;Akitsu et al, 1997;Akitsu & Einaga, 2005). As a continuation of our research devoted to the design and synthesis of complexes with 5,5-diphenylhydantoinate (Hu et al, 2006(Hu et al, , 2007(Hu et al, , 2009, we report here the crystal structure of the title compound.…”
Section: N′)cobalt(ii)mentioning
confidence: 95%
“…Xilan Hu, Qing Jiang, Daqi Wang and Haifeng Liu S1. Comment 5,5-Diphenylimidazoline-2,4-dione (phenytoin) is a widely used drug in the treatment of epilepsy and an excellent ligand for transition metal complexes (Milne et al, 1999;Akitsu et al, 1997;Akitsu & Einaga, 2005). As a continuation of our research devoted to the design and synthesis of complexes with 5,5-diphenylhydantoinate (Hu et al, 2006(Hu et al, , 2007(Hu et al, , 2009, we report here the crystal structure of the title compound.…”
Section: N′)cobalt(ii)mentioning
confidence: 95%
“…For general background see Akitsu et al (1997), Milne et al (1999). For related structures see Akitsu & Einaga et al (2005); Hu et al (2006a,b).…”
Section: Related Literaturementioning
confidence: 99%
“…In the solid state, most of these complexes afford a four-coordinated square-planar CuN 4 coordination geometry (Akitsu, Komorita & Urushiyama, 2001) with the aid of crystal-packing forces. Appropriate steric factors of the ligands can lead to a tetrahedrally distorted square-planar CuN 4 coordination geometry (Akitsu et al, 2003) or a ®ve-coordinated square-pyramidal CuN 4 O coordination geometry (Akitsu et al, 1997). To date, structural regulation by other means, such as solvent in the crystal (Tynan et al, 2004), has not been observed for analogous complexes.…”
Section: Commentmentioning
confidence: 99%
“…The CuÐN bond distances (Table 1) are within the range found in related complexes, some of which are planar and some of which exhibit some tetrahedral distortion, viz. the CuÐN(imide) distances range from 1.975 (5) to 2.05 (1) A Ê , whereas the CuÐN(amine) distances range from 1.97 (1) to 2.030 (4) A Ê (Akitsu, Komorita & Kushi, 2001;Akitsu et al, 2003;Akitsu & Einaga, 2004). The cis-N1Ð Cu1ÐN3 angles are close to being right angles.…”
Section: Commentmentioning
confidence: 99%